Internal Migration Patterns of Natives and Foreigners in Spain - Bunea, Daniela (Richtmann Publishing, 2012)
As a consequence of strong international immigration, Spanish statistical data offer the possibility to distinguish betweenpatterns of migration for both natives and foreigners. The objective of this paper is to determine the difference in patterns between thesetwo categories as regards their migration within Spanish borders. The period of analysis is mainly 2003-2010, the level of aggregation isNUTS 3 (provincial) and the method of research is a quantitative comparative analysis. The study is divided in the following areas ofinterest: intra and inter-provincial flows; gross and net migration; migration by sex, by age, by source/destination size, and by nationality.Also, I try to find out if migrants are more attracted by leading provinces and if the hypothesis of social networking for foreign-bornmigrants is confirmed. The main results reveal: a greater propensity of foreign-born migrants to make long-distance movements; grossmigration rates of foreigners much higher than nativesÂ´; both natives and foreigners (more) are attracted by prosperous provinces;foreign out-migrants are less willing to leave provinces with high concentration of foreign-born population while foreign in-migrants prefersuch provinces, i.e. social networking is true; foreign males migrate more than foreign females while the difference between Spanishsexes is rather inexistent; foreigners and Spaniards have also different age propensities to migration, although with some similarities;Spaniards and foreigners also differ when referring to the size of the province they come/go from/to. And finally, the paper makes aranking of migration by groups of nationality.